Effects of smoking on the level of sp-a and sp-d surfactant proteins in the blood of patients without bronchopulmonary diseases - O. S. Kharlamovа; K. Yu. Nikolaev; Yu. I. Ragino; M. I. Voevoda (Бюллетень сибирской медицины, 2020)
Every year, about six million people die from tobacco use. Respiratory epithelium is the first line of defense against exogenous invasion, in particular, harmful inhaled particles, pathogens and allergens. However, the epithelium of the respiratory tract is also a regulator of immunological and inflammatory reactions through secretion of inflammation and immune cell recruitment mediators. An important component of the pulmonary immune system is the surfactant, and, in particular, its proteins SP-A and SP-D, synthesized mainly by type II pneumocytes.Aim. To assess the levels of surfactant proteins SP-A and SP-D in the blood of smoking patients without bronchopulmonary diseases.Materials and мethods. The study included 59 patients admitted to the department of internal medicine with hypertension. The general group was divided into subgroups: non-smoking patients (n = 31) and healthy smokers (n = 28). All patients underwent clinical, functional, diagnostic and laboratory tests. The content of surfactant proteins SP-A and SP-D in the blood was determined by enzyme immunoassay.Results. The subgroups did not differ in sex, age, height, body weight, blood pressure, heart rate, respiratory rate, and the distribution of comorbidities. The subgroups differed in the platelet level; in other main parameters of complete blood count and blood biochemistry no differences were revealed. It was found that the blood levels of surfactant proteins SP-A and SP-D in the subgroup of healthy smokers were significantly higher in comparison with the subgroup of non-smoking patients. The correlation analysis revealed a direct relationship between surfactant proteins SP-A and SP-D and smoking (R = 0.360, p = 0.006, R = 0.274, p = 0.037), a negative correlation between SP-D protein and age (R = –0.315, p = 0.016), and a direct relationship between SP-A protein and diastolic blood pressure (R = 0.271, p = 0.039). In the non-smoking subgroup, a negative correlation between SP-D and age (R = –0.438, p = 0.016) and between SP-D and systolic blood pressure (R = –0.433, p = 0.017) was identified.Conclusion. The direct relationship between higher levels of the surfactant proteins SP-A and SP-D and smoking in the group of healthy smokers is justified (inflammatory changes, structural abnormalities in the lung parenchyma under the influence of cigarette smoke). The SP-D protein is more significant in comparison with the SP-A protein in vascular wall remodeling, lung tissue matrix, oxidative lung tissue damage, and apoptosis, which explains its negative correlation with age and systolic blood pressure.